Innovative probiotic fermentation approach for zearalenone detoxification in dried distiller’s grains - Murtaza, Bilal; Guo, Ling-ling; Wang, Lili; Li, Xiaoyu; Zeb, Liaqat; Jin, Bowen; Li, Ji-bin; Xu, Yongping (Frontiers in Microbiology, 2025)
Zearalenone (ZEN) contamination in dried distiller’s grains and solubles (DDGS) poses serious health risks and economic losses in animal farming. This study aimed to evaluate the effectiveness of probiotic fermentation using Lactobacillus plantarum CN1 in detoxifying ZEN and optimizing fermentation conditions for maximum efficiency. L. plantarum CN1, identified with 99% genetic homology, was used for DDGS fermentation. The detoxification mechanism was analyzed through adsorption assays, post-heat treatment effects, and scanning electron microscopy (SEM). ZEN removal was assessed over 72 h under various conditions, including bacterial concentration, temperature, and pH optimization. The results showed that CN1 achieved a maximum ZEN removal rate of 69% within 72 h, with an optimized efficiency of 75.6% at 4 × 109 CFU/mL. Over 60% of ZEN was adsorbed by the bacterial cell wall, while removal in the fermentation supernatant and intracellular fluid remained below 5%. Scanning electron microscopy (SEM) analysis highlighted structural changes in the bacterial cells, particularly elongation and thinning, with more pronounced cell damage observed following heat and ZEN treatment. These modifications may explain the varying adsorption efficiencies observed. Heat treatment, particularly autoclaving, significantly enhanced adsorption efficiency to 82.9%, whereas acid and alkali treatments reduced it. Fermentation also improved the nutritional quality of DDGS, increasing crude protein by 7.16%, reducing crude fiber by 0.65%, and lowering pH to 4.3. These findings demonstrate that probiotic fermentation with CN1 offers a promising, cost-effective strategy for mitigating ZEN contamination while enhancing DDGS quality. Future studies should explore large-scale applications and the potential of CN1 in multi-mycotoxin detoxification to further improve feed safety.